Evaporation Climate Zonation Based on Observation Data in Indonesia Using Cluster Analysis. Issue 1 (November 2021) - Putra, I D G A; Perdana, R B; Sopaheluwakan, A; Suryadi
Abstract: Identification of regional evaporation zones is very important because information on the classification of evaporation patterns in an area can be used for various purposes, one of which is knowing the amount of water in the reservoir that is lost due to evaporation. In this study, the evaporation zone in Indonesia was created using cluster analysis. The evaporation data from 127 BMKG observation stations for 6 years from 2014 to 2019 were used after the normal monthly calculation was then standardized with mean = 0 and standard deviation = 1 to ensure that all variables were given the same weight so that it became the 127 x 12 matrix used in the analysis. Hierarchical cluster analysis was chosen to regionalize evaporation. Five different techniques are applied to initially determine the most suitable method for the area. Cluster stability is also tested. It was decided that the Ward method is the most likely to produce acceptable results in this evaporation variable. 3 different classifications of evaporation zones are found in Indonesia. Evaporation zone 1 forms a seasonal cycle with one peak evaporation that occurs with the highest peak occurring in August and the minimum evaporation occurring in February in areas in the northern and central regions of Sumatra island, eastern Kalimantan, parts of Java island, North Sulawesi and West Papua. Evaporation zone 2 forms a seasonal cycle with two peaks that occur in December and March and minimum evaporation occurs in June which is in the southern region of the island of Sumatra, almost the entire island of Kalimantan, a small part of the island of Java, central Sulawesi, the archipelago. Maluku as well as the northern island of Papua. Evaporation zone 3 forms a seasonal cycle with one peak evaporation that occurs in October and the minimum evaporation occurs in June which is in a small area of the island of Central Sumatra, South Kalimantan, the west coast of Sulawesi, and all parts of the island of Nusa Tenggara.